Clinical Outcomes After Aggressive Active Early Motion and Modified Kleinert Regimens: Comparison of 2 Consecutive Cohorts. (March 2023) - Jokinen, Kaisa; Häkkinen, Arja; Luokkala, Toni; Karjalainen, Teemu
Background: Modern multistrand repairs can withstand forces present in active flexion exercises, and this may improve the outcomes of flexor tendon repairs. We developed a simple home-based exercise regimen with free wrist and intrinsic minus splint aimed at facilitating the gliding of the flexor tendons and compared the outcomes with the modified Kleinert regimen used previously in the same institution. Methods: We searched the hospital database to identify flexor tendon repair performed before and after the new regimen was implemented and invited all patients to participate. The primary outcome was total active range of motion, and secondary outcomes were Disabilities of Arm, Shoulder, and Hand; grip strength; globally perceived function; and the quality of life. Results: The active range of motion was comparable between the groups (mean difference = 14; 95% confidence interval [CI], −8 to 36; P = .22). Disabilities of Arm, Shoulder, and Hand; grip strength; global perceived function; and health-related quality of life were also comparable between the groups. There was 1 (5.3%) rupture in the modified Kleinert group and 4 (15.4%) in the early active motion group (relative risk = 0.3; 95% CI, 0.04-2.5; P = .3). Conclusions: Increasing active gliding with a free wrist and intrinsic minus splint did not improve the clinical outcomes after flexor tendon injury at a mean of 38-month follow-up.